Peningkatan Kesadaran Sosial-Budaya Masyarakat Berbasis Kegiatan Sosial-Keagamaan - Fauziyah, Nurul Khansa; Hikmah, Nurul; Aziz, Abdul; Erna, Erna; Fajrunnura, Fajrunnura; Tambunan, Rini Muhairoh (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2022)
Aceh Province is one of the provinces that has significant characteristics and these characteristics are the pride of the community. One of the most distinctive in the life of the Acehnese people is a lifestyle that has the nuances of Islamic religion. Moreover, in Lhokseumawe City, which has the origins of the Islamic kingdom of Samudera Pasai, it still upholds religious values. This Community Service uses a direct approach method to the village head and the community. The activities carried out are; (1) guidance of Tahsinul Qur'an, (2) practical guidance a dzan to children, (3) m engadakan recitation of the Qur'an, Iqra', tajwid science, and other religious sciences to children in meunasah, (4) g otong royong in the geuchik office environment, ronda and meunasah posts, also in the street area of Gampong Blang Teue, (5) organizing religious competitions for children. After implementing the Community Service program from mid-January to the end of February 2022, it is hoped that the community in Blang Teueuu Village, especially children, will be more enthusiastic in maintaining socio-cultural values in the frame of routine religious activities. To maintain the socio-cultural values of society, comprehensive efforts are needed so that citizens can wisely filter out new cultures that have the potential to undermine socio-cultural values. Likewise, the public must still be open to new information and technology so as not to be left behind in the development process in general.